Systematic analysis of factors associated with progression and regression of ulcerative colitis in 918 patients. Issue 5 (6th July 2015) - Safroneeva, E.; Vavricka, S.; Fournier, N.; Seibold, F.; Mottet, C.; Nydegger, A.; Ezri, J.; Straumann, A.; Rogler, G.; Schoepfer, A. M.; the Swiss IBD Cohort Study Group; Bauerfeind, Peter; et al.
Summary Background Studies that systematically assess change in ulcerative colitis (UC) extent over time in adult patients are scarce. Aim To assess changes in disease extent over time and to evaluate clinical parameters associated with this change. Methods Data from the Swiss IBD cohort study were analysed. We used logistic regression modelling to identify factors associated with a change in disease extent. Results A total of 918 UC patients (45.3% females) were included. At diagnosis, UC patients presented with the following disease extent: proctitis [199 patients (21.7%)], left‐sided colitis [338 patients (36.8%)] and extensive colitis/pancolitis [381 (41.5%)]. During a median disease duration of 9 [4–16] years, progression and regression was documented in 145 patients (15.8%) and 149 patients (16.2%) respectively. In addition, 624 patients (68.0%) had a stable disease extent. The following factors were identified to be associated with disease progression: treatment with systemic glucocorticoids [odds ratio (OR) 1.704, P = 0.025] and calcineurin inhibitors (OR: 2.716, P = 0.005). No specific factors were found to be associated with disease regression. Conclusions Over a median disease duration of 9 [4–16] years, about two‐thirds of UC patients maintained the initial disease extent; the remaining one‐third had experienced either progression or regression of the disease extent.